Elos da memória: o discurso dos avós sobre a cultura - Minuzzi, Ivi Helena (My University, 2014)
This study has the objective of analyzing, through elderly s memories and memory literary, the cultural manifestations present in the ties of grandparents and grandchildren. For that, to prioritize three text where the narrator remembers its life. It was taken excerpts from literatures that represent the memory work about grandparents and the relation of the memory with culture and family. The writings were: Solo de Clarineta from Érico Verissimo, Menino de Engenho from José Lins do Rego and Infância from Graciliano Ramos. Was made a qualitative research, in what it was set the content analysis of narrative interviews of elderly grandparents that remembered of their grandparents and grandchildren. From this analysis, five categories and subcategories were made that synthesize the content of the speeches: the first category is called: Places to be together and it has a subcategory called: Pictures of the places; the second is called: The role of the grandparents and it has the subcategory Protection means; the third is called Cultural features and its subcategories are: Grandparents knowledge and Religion practices; the fourth category is called Belonging feeling and it has the subcategories Origin history and Differences and marks, finally the fifth category, that is called Life recognition and it has the ideas of limits and possibilities. This dialogue between the interviewed and the literary narratives could make it to be understood dynamically the collective memory in the family tie and to discuss the importance of grandparents as cultural representants.
Este estudo tem como objetivo analisar, através da memória de idosos e da memória literária, as manifestações culturais presentes no vínculo entre avós e netos. Para tal, foram privilegiadas três obras em que o narrador lembra de sua vida, os excertos das obras literárias representam o trabalho da memória sobre os avós e as relações da memória com a família e a cultura. As obras escolhidas foram: Solo de Clarineta de Érico Verissimo, Menino de Engenho de José Lins do Rego e Infância de Graciliano Ramos. Também foi realizado um estudo qualitativo em que se aplicou a análise de conteúdo nas entrevistas narrativas de idosos-avós que lembravam de seus avós e de seus netos. Dessa análise foram construídas cinco categorias e subcategorias que sintetizaram o conteúdo dos discursos: a primeira categoria chama-se Espaços de Convivência e tem uma subcategoria chamada Retrato dos Lugares; a segunda chama-se Papéis dos Avós e engloba a subcategoria Meios de Proteção; a terceira é Traços Culturais e tem como subcategorias Sabedoria dos Avós e Práticas Religiosas; a quarta categoria chama-se Sentimento de Pertença e tem a subcategoria Histórias de Origem e Marcas e Diferenças, a quinta categoria chama-se Re(-)conhecimento da vida e engloba as idéias de Limites e Possibilidades. O diálogo entre o discurso dos entrevistados e as narrativas literárias possibilitou compreender dinamicamente a memória coletiva no vínculo intergeracional e discutir a importância dos avós como representantes da cultura.
Keywords: Literatura brasileira; Literatura; Memória coletiva; Cultura regional; Vínculo; Relações intergeracionais; Idosos; Érico Verissimo; Solo de clarineta: memórias (Obra literária, 1973); Literatura brasileira; José Lins do Rego; Menino de engenho (Obra literária, 1932); Crítica literária; Graciliano Ramos, 1892-1953; Infância (Obra literária, 1945); Literature; Collective memory; Ties; Relations between generations